2009
DOI: 10.1099/vir.0.014613-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neutrophil extracellular traps in cats naturally infected with feline leukemia virus

Abstract: Feline leukemia virus (FeLV), a common, naturally occurring gammaretrovirus in domestic cats, is associated with degenerative diseases of the haematopoietic system, immunodeficiency and neoplasia. FeLV infection causes an important suppression of neutrophil function, leading to opportunistic infections. Recently, a new microbicidal mechanism named NETosis was described in human, bovine and fish neutrophils, as well as in chicken heterophils. The purpose of the present study was to characterize NETosis in felin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 30 publications
(32 reference statements)
5
75
0
2
Order By: Relevance
“…1 and 2), we infer that signaling downstream of CD18 is important for bovine neutrophil DNA release. Previous reports have demonstrated that neutrophils from several vertebrate species, human eosinophils and mast cells, and chicken heterophils all form extracellular traps (12,13,19,34,38,43,48,49,68,73). All these cells express CD18, which is involved in transendothelial migration of leukocytes from the bloodstream into tissue at sites of infection (45,47,54,60,61,75).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2), we infer that signaling downstream of CD18 is important for bovine neutrophil DNA release. Previous reports have demonstrated that neutrophils from several vertebrate species, human eosinophils and mast cells, and chicken heterophils all form extracellular traps (12,13,19,34,38,43,48,49,68,73). All these cells express CD18, which is involved in transendothelial migration of leukocytes from the bloodstream into tissue at sites of infection (45,47,54,60,61,75).…”
Section: Discussionmentioning
confidence: 99%
“…72,73 The mechanisms of neutrophil-mediated antiviral activity remain undefined, although new evidence suggests that viruses can stimulate NET release. 24,25,74,75 Recently, superresolution structured illumination microscopy directly demonstrated that HIV elicits NETs through PMN-expressed TLR7 and TLR8. Here, HIV particles attached to NETs and were liberated following DNase treatment.…”
Section: Trappingmentioning
confidence: 99%
“…The role of NETs in viral infections is not yet clear. However, some viruses induce the release of NETs [14,15].…”
Section: Beneficial and Deleterious Effects Of Neutrophil Extracellulmentioning
confidence: 99%